The Context of Caution: An Examination of Age, Social Context, and Sex on Measures of Inhibitory Control and Risky Decision-Making. (January 2020) - Cowell, Raquel A.; Paitel, Elizabeth R.; Peters, Sierra
Understanding how older adults successfully navigate complex choices like driving requires the consideration of processing speed, inhibitory control, attentional processes, and risk management, and the context within which these decisions occur. The current study employed the Flanker task, the Stoplight task, and a personality inventory with 43 younger adults and 49 older adults either while they were alone or being observed by two same-sex, similarly aged peers. On the Flanker task, older adults performed more slowly, but with comparable accuracy. On the Stoplight task, there was a significant main effect of Context, and an Age-Group by Sex interaction, even after controlling for response time: All groups had a greater number of crashes when alone, and young adult males had significantly more crashes than any other group. These results emphasize the importance of considering the broader context of decision-making.